1996
DOI: 10.1002/anie.199625661
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Protonation of Enolates and Enols

Abstract: Enantioselective protonation, until recently a largely overlooked reaction, has, in the last five years, developed into a field of intense research activity. The progress achieved parallels or complements that obtained in the understanding of enolate structures and reactivities. The conceptual simplicity and attractiveness of enantioselective protonation results from the fact that after reaction, the chiral proton donor is regenerated in its original protonated form by an extractive workup. Enantioselective pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(77 citation statements)
references
References 121 publications
0
76
1
Order By: Relevance
“…More recently, this strategy has been refined to instead generate a chiral Pd-enolate intermediate from allyl β-ketoester substrates (e.g., 104 and 107 , Figure 7c) in the hopes that chirality at the metal might impart improved stereocontrol in the protonation step and obviate the need for heterogeneous Pd catalysts. Stoltz and coworkers 69 found that the catalyst derived from Pd(OAc) 2 and phosphinooxazoline (PHOX) ligand 105 was capable of achieving enantioselective protonation in the presence of formic acid and molecular sieves (MS). High enantiomeric excesses were obtained for a range of cyclic ketone products including tetraloneand cyclohexanone-derived ketones (e.g., 106 and 109).…”
Section: Enantioselective Protonation By Means Of Chiral Brønsted Basementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, this strategy has been refined to instead generate a chiral Pd-enolate intermediate from allyl β-ketoester substrates (e.g., 104 and 107 , Figure 7c) in the hopes that chirality at the metal might impart improved stereocontrol in the protonation step and obviate the need for heterogeneous Pd catalysts. Stoltz and coworkers 69 found that the catalyst derived from Pd(OAc) 2 and phosphinooxazoline (PHOX) ligand 105 was capable of achieving enantioselective protonation in the presence of formic acid and molecular sieves (MS). High enantiomeric excesses were obtained for a range of cyclic ketone products including tetraloneand cyclohexanone-derived ketones (e.g., 106 and 109).…”
Section: Enantioselective Protonation By Means Of Chiral Brønsted Basementioning
confidence: 99%
“…Emphasis has been placed on recently developed methods and their accompanying mechanisms in order to update the most recent prior reviews on this topic. 2,3,4,5,6,7,8 Each method relies on particular stereochemical control elements based on the mechanism of the protonation transformation. Appreciation of these controlling elements may lead to improved methods for preparing valuable chiral materials for a variety of synthetic applications.…”
mentioning
confidence: 99%
“…The present asymmetric protonation reaction is unique in the term of catalytic amount of lithium. Generally in the asymmetric protonation reaction, stoichiometric amounts of metal enolate and chiral source are used, [62][63][64] and the use of the catalytic amount of lithium is a challenging task. 37,40,48,49,65,66) The reaction of methyl atropate 14 (R=Ph) with 2e in the presence of 8 mol% of 8 gave protonation product 15 (R=Ph) in quantitative yield with 92% ee.…”
Section: Stereochemistry Of Protonation Process 55)mentioning
confidence: 99%
“…[1][2][3][4][5][6] Over the past years, we contributed to this topic using various substrates and procedures. 7 With 2-methyl-2-benzyloxycarbonyl-1-indanone (KE) as the substrate, the procedure, studied in collaboration with Martens team, 8,9 involves a Pd-catalyzed hydrogenolysis in the presence of an unichiral 10 β-aminoalcohol (AH*) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%